Thermomechanical study of lead-free solder joints and the effects of carbon-based additives - Tan, Khai Shiang (2019)
The trend of miniaturization is inevitable in the electronics assembly. However, scaling down of the electronics assembly does not only involve the components substrate and packaging, the solder balls dimension and pitch size need to be taken into account as well. In the first part of the study, the thermomechanical behaviour of a M.2 form factor solid-state drive (SSD) is studied with finite element analysis (FEA). The SSD is a single assembly, modelled with $ NANDs attached on top, each with a 132-BGA connection of lead free solder (SAC305). The sample is subjected to thermal load at 125° C. The effects of NANDs attachment on the overall structure deformation and induced stress are investigated. The effect of scaling down of the NAND size on the stress generated at the solder joints is also studied. Based on the FEA model and the results from shadow Moire Measurement, the stress generated on a physical M.2 sample are analysed. In the second part of the work, the effect of carbon-based additives in SAC305 is investigated.